Prosthetic Treatment for Hemimaxillectomy Patient: (A Clinical Case) - Nashwah Subhi; Mohammed A Abdulla; Nadira A Hatim (University of Mosul, College of Dentistry, 2018)
Aims: prosthetic rehabilitation of a maxillary defect after hemi-maxillectomy with a palatal obturator made from nickel chromium framework. Materials and methods: A silicon impression was made and poured with a dental stone to develop a definitive cast. The site, position and shape of maxillary defect determine the path of insertion. Design the metal framework of the obturator to Class II R.P.D according to Kennedy's classification. Casting the framework in base-metal alloy made from nickel chromium framework, centric jaw relation was recorded. A finished prosthesis (an obturator of closed hollow-bulb type) was inserted. Conclusions: Obturator prosthesis enhancing function and speech, reduce the rate of fluids and food passing to the nose. Extend the border of an acrylic of the prosthesis at defect site lead to enhance both the retention and stability of the obturator.